Minimal dose, maximal scrutiny: A critical appraisal of the feasibility and functional implications of a reduced-volume Nordic hamstring exercise protocol - Yang, D. J.; Yang, J.; Xu, H. L.; Wang, G. Y. (Scandinavian Journal of Medicine & Science in Sports, 2025)
To the Editor, We read with great interest the study by Miura and Miyamoto [1], which explores whether a substantially reduced volume of Nordic Hamstring Exercise (NHE) can preserve key adaptations while potentially reducing muscle stiffness. The investigation of minimal effective training doses represents an important and practical direction for sports science. In the spirit of constructive scholarly exchange, we wish to offer several reflections that may help contextualize the findings and inspire future research [1, 2].